THE CREATIVE WORKS OF ABDULQADIR GIYLANI AND QADIRIYA - Gulandom Samievna Yunusova; Qodirova M. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Abu Muhammad Muhyiddin Abdulqadir ibn Abu Salih Sheikh Abdulqadir Giylani, one of the people who left an indelible mark on the history of mysticism and became known as a great man in the life of the people, and who is remembered in the works of many poets and scholars, is a descendant of the Prophet (saas). He was born in 470 A.D. (1079 A.D.) in the present-day city of Gilan in present-day Iran, and died in Baghdad in 561 A.D. (1166 A.D.). The tomb in this city is now a crowded shrine. Alisher Navoi in his book "Nasayim - ul muhabbat" informs that Sayyid Abdulqadir Giylani was born in a place called "Bashtiz" in Gilan region. There was a place called Tabaristan (Iran) known as Gilon (Jilon), Gilon or Gil. Jil is close to the Tigris. It’s a one-day drive from Baghdad. "Jil" is close to Madyan. These two places are called Gili, Giylani and Jiyloni. Many say that Hazrat Abdulqadir Giylani touches two areas. Navoi writes in the book "Ravzat-un navodir" that this is a mistake. He lived in these areas for a short time. He is originally from Gilon.